Assessment of vırulence patterns and pathogenıcıty-related genes of Colletotrichum falcatum Went in Bangladesh - Hossain, Md Imam; Vadamalai, Ganesan; Saad, Norsazilawati; Mohd Hata, Erneeza; Khaiyam, Md Omar; Rahman, Muhammad Ziaur; Kutawa, Abdulaziz Bashir; Mohd Zobir, Syazwan Afif; Ahmad, Khairulmazmi (Springer Nature Switzerland, 2022)
Sugarcane (Saccharum officinarum L.) is one of the important cash crops and the main source of white sugar in tropical and sub-tropical regions. Colletotrichum falcatum Went is the causative agent of sugarcane red rot disease worldwide. This pathogen is diverse in pathological and molecular characteristics. This study is aimed to assess the vırulence patterns and role of pathogenıcity-related genes of C. falcatum Went. A total of 41 isolates were isolated from four sugarcane major growing regions of Bangladesh from 2018 to 2019 cropping seasons. The virulence test field experiment was conducted at Bangladesh Sugarcrop Research Institute (BSRI) research farm in randomized completely block design (RCBD) with three replications from January to December in 2019 and 2020. The pathogenicity-related gene molecular experiments were carried out at the Bacteriology Laboratory, University Putra Malaysia (UPM). The assessment of disease parameters was based on the published procedures. Out of 41 isolates, three isolates were virulent,18 isolates were moderately virulent and 13 isolates were the least virulent. The rest of the seven isolates had demonstrated different virulence attributes in the assessment periods. All C. falcatum isolates possessed PKS1, HXT1, and Pel2 genes and had a high similarity value but showed variation among the virulent, moderately virulent, and the least virulent isolates. Nucleotide substitutions and deletions in some loci are the possible causes of variation among them.These findings would help in understanding the variability of C. falcatum isolates based on sugarcane differential hosts, and the role of pathogenicity-related genes during pathogenesis.